Pelatihan Membuat Konten Yang Menarik Untuk Pemasaran Interaktif Di Media Sosial Pada Anggota Fatayat NU Ciledug - Rosiana Andhikasari; Abdul Aziz; Arina Muntazah; Rindana Intan Emeilia (CV. ITTC INDONESIA, 2022)
Social media is an effective tool for advertising activities. Competition in the world of advertising on social media is getting higher along with the rapid increase in social media users. The impact was also felt by mothers who are members of the Ciledug Fatayat NU (Nahdlatul Ulama) organization. An effective communication strategy is needed in marketing activities, especially promotion and advertising in order to be able to provide effective and accurate information about Fatayat NU Ciledug. This community service activity increases the knowledge and skills of the participants, namely members of Fatayat NU Ciledug regarding marketing, namely effective promotion and making attractive advertisements on social media, so as to increase public understanding of Fatayat NU Ciledug.